Peripheral Nerve Blocks for Surgery About the Knee. Issue 12 (6th December 2016) - Howell, Richard; Hill, Brenton; Hoffman, Christopher; Treacy, Erin; Mulcahey, Mary K.
Abstract : Peripheral nerve blocks are an often-utilized and efficacious method of analgesia for orthopaedic surgery about the knee. Benefits include decreased pain and narcotic use, increased participation in postoperative physical therapy, and decreased length of hospital stay. Adductor canal blocks have the advantage of preserving quadriceps function for early postoperative range of motion and walking. The risk of serious complications resulting from a peripheral nerve block is relatively low, ranging from 0% to 3%.